(untitled) (Revista de Estudos da Linguagem, 2006)
This is an experimental study which aimed at investigating theralationsship between working memory capacity and measuresof L2 speech performance in a picture description task. The mainassumption underlying the present study was that L2 speaking isa complex cognitive task which is carried out within theconstraints of a limited-capacity system, namely, working memory.In this system, there are trade-off effects between the storage andprocessing functions of working memory just as in L2 speakingthere are trade-off effects among fluency, accuracy and complexitywhen L2 learners perform under processing pressure.